2022
DOI: 10.1080/2578983x.2022.2051306
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intimate partner violence among native and immigrant male partners in Sweden

Abstract: This study aimed to examine the importance of differentiating between partner violent men in terms of immigrant or native Swedish background, when assessing risk for intimate partner violence (IPV) recidivism. A quantitative design was used with a sample of 1263 alleged male perpetrators reported for IPV-related crimes to the Swedish police. Data consisted of police officers' risk assessments using the Swedish version of the Brief Spousal Assault Form for the Evaluation of Risk (B-SAFER). Results showed that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…For instance, a study in Vietnam revealed that partner's behaviors supporting male domination, alcohol misuse, and witnessing violence during childhood were risk factors for perpetrating IPV [28]. Additionally, a study in Sweden determined that partner migration background is a relevant factor altering women's IPV victimization risks [29]. Further studies corroborating these results can be found in [30] with data from Sub-Saharan African countries, in [31] focusing on Turkey, and in [32] examining the Chinese context.…”
Section: Individual-level Factorsmentioning
confidence: 99%
“…For instance, a study in Vietnam revealed that partner's behaviors supporting male domination, alcohol misuse, and witnessing violence during childhood were risk factors for perpetrating IPV [28]. Additionally, a study in Sweden determined that partner migration background is a relevant factor altering women's IPV victimization risks [29]. Further studies corroborating these results can be found in [30] with data from Sub-Saharan African countries, in [31] focusing on Turkey, and in [32] examining the Chinese context.…”
Section: Individual-level Factorsmentioning
confidence: 99%